PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS APLIKASI LECTORA INSPIRE PADA PEMBELAJARAN AKUNTANSI SEBAGAI UPAYA MENINGKATKAN BELAJAR MANDIRI SISWA SMK - Shelviyani, Dea Vitta; Santoso, Sigit; Muchsini, Binti (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe Purposes of this research are: (1) providimg a decent of the game education media based on lectora inspire application; and (2) investigate the effectiveness of the game education media based on lectora inspire application in accounting learning as an effort to improve self-directed learning students of vocational high school. The methods of this research are research and development method. Its samples were students in grade X Accounting A and grade X Accounting B as control class and experimental class by random sampling technique. Procedure of the developing game education media based on lectora in-spire application referred to the one claimed by Borg and Gall with some modification. Data of the re-search were collected through questionnaire, feasibility sheet and response sheet.. they were validated by using content validition and construct validition. And analyzed by using the statistical descriptive analysis to investigate the level of self-directed learning and the game education media feasibility, followed with the statistic inferential analysis to investigate the effectiveness of the game education media. The result of the research shows that game education media based on lectora inspire application is feasible to be used base on validation of a media expert (97,4%), a material expert (89,8%), a practitioner (83,8%), and stu-dent assessment (91,6% ) Which are categorized as "Good" and "Very Good" based on the guildelines of quantitative to qualitative score eligibility criteria. In addition, the developed of game education media based on lectora inspire application is effective to improve the self-directed learning of the students as indicated by the p-value = 0,0000 <0.05.Keywords: Game education media, Lectora Inspire, Self-Directed Learning.ABSTRAKPenelitian ini bertujuan untuk: (1) Menyediakan media game edukasi yang layak berbasis aplikasi lectora inspire; dan (2) Mengetahui kefektifan media game edukasi berbasis aplikasi lectora inspire pada pembelajaran akuntansi sebagai upaya meningkatkan belajar mandiri siswa SMK. Metode penelitian yang digunakan adalah metode penelitian dan pengembangan. Subjek penelitian adalah siswa kelas X Akuntansi A dan X Akuntansi B sebagai kelas kontrol dan kelas eksperimen yang diambil dengan teknik random sampling. Prosedur pengembangan media game edukasi berbasis aplikasi lectora inspire dilakukan berdasarkan langkah-langkah pengembangan menurut Borg and Gall dengan modifikasi. Pengumpulan data dilakukan dengan instrumen berupa angket, lembar kelayakan dan lembar respon. Validitas instrumen menggunakan validitas isi dan kontruk pada angket belajar mandiri. Analisis data menggunakan analisis statistik deskripstif untuk mengetahui tingkat belajar mandiri dan kelayakan media game edukasi, kemudian dilanjutkan analisis statistik inferensial untuk mengetahui keefektifan media game edukasi. Hasil penelitian menunjukan bahwa media game edukasi berbasis aplikasi lectora inspire layak digunakan berdasarkan validasi ahli media (97,4%), ahli materi (89,8%), praktisi (83,8%), serta penilaian siswa (91,6%) yang termasuk kategori âBaikâ dan âSangat baikâ berdasarkan pedoman kriteria kelayakan skor kuantitatif ke kualitatif. Media game edukasi berbasis aplikasi lectora inspire efektif meningkatkan belajar mandiri siswa (p = 0,0000 < 0,05).Kata lunci : Media game edukasi, Lectora Inspire, Belajar mandiri